The potential correlation between patient-reported symptoms and the use of additional haemostatic medication for joint bleeding in haemophilia patients with inhibitors: a post hoc exploratory analysis of recombinant activated factor VII data from the ADEPT2 trial. Issue 3 (April 2017) - Lentz, Steven R.; Rangarajan, Savita; Karim, Faraizah A.; Andersen, Philip D.; Arkhammar, Per; Rosu, Gabriela; Mahlangu, Johnny
Abstract : N/A: Haemophilia treatment guidelines advocate early home-based treatment of acute bleeds. In the ADEPT2 trial, data were collected on the home treatment of bleeds with recombinant activated factor VII (rFVIIa) in haemophilia patients with inhibitors and self-reported bleeding-related symptoms. A total of 93% of all bleeds, and 91.5% of joint bleeds, were treated successfully with one to three doses of 90 μg/kg rFVIIa. However, some patients self-administered additional haemostatic medication (AHM) up to 48 h after the first rFVIIa treatment. The aim of this trial was to investigate the relationship between patient-reported symptoms, time to treatment initiation, and the use of AHM. A post hoc analysis was conducted on 177 joint bleeds and the patient-reported categorical symptoms of pain, swelling, mobility, tingling, and warmth, and the pain visual analogue scale (VAS) score. Analyses were descriptive and used logistic regression modelling. Complete symptom data were available for 141, 136, and 129 joint bleeds at 0 or 1, 3, and 6 h, respectively. Pain and pain VAS assessments were the best predictors of AHM use. Patients who self-administered AHM had higher mean pain VAS scores at each time point; both pain and pain VAS scores declined over time. Time to treatment initiation was an independent predictor for AHM use. Higher initial pain scores and longer time to treatment were the best predictors for administration of AHM. The observation that some patients chose to self-infuse in the face of declining levels of pain warrants further study to better understand the reasons behind patient decision-making.